The influence of accountability, transparency, affective and cognitive trust toward the interest in paying zakat - Mohammad Fahmi Ikhwandha; Ataina Hudayati (Jurnal Akuntansi dan Auditing Indonesia, 2019)
This research aimed to expand the previous study by studying the role of two dimensions of trust concepts namely affective trust and cognitive trust. Particularly, this research aimed to analyze the influence of accountability and transparency toward affective and cognitive trust. Moreover, the purpose of this research was to test the influence of cognitive and affective trust toward the interest in paying zakat through zakat institution. The subject of this research was 100 muzakkis of BAZNAS (Badan Amil Zakat Nasional/National Board of Zakat) located in Special  Region of Yogyakarta and BAZNAS located in Yogyakarta City. The data analysis method used in this research was Partial Least Square. The result of this study implied that accountability positively affects affective and cognitive trust. Furthermore, the result of this study also implied that affective and cognitive trust positively affects the interest in paying zakat through zakat institution. In other hand, this research also found that transparency has no effect on cognitive and affective trust.